Study on students' accessibility to the National Science and Engineering Complex in UP Diliman - Baluyot, Daniel E.
This research aims to show the analysis of the accessibility of the National Science Complex and Engineering Complex. Detailed student trip pattern derived from the travel diary will provide the usage of all modes of transportation when accessing the study area. It will also help to determine the location of direct routes or shortcuts that the students are using in order to gain their access to different buildings. Meanwhile, the travel demand survey will produce the students' perception rating of the different features of transportation system in the study area. This will show whether the existing transport facilities are enough for the access of the students. Furthermore, this will lead to the recommendation on the improvement of the accessibility of the study area. Upon gathering these data, 68% of the students have less than 15 minutes travel time when going to their classes in the study area. The 15-minute time interval was adopted from the university rule. This research aims for the increase of percentage if not 100% accessibility of students. Construction of concrete pavement along shortcuts, proper signage in the location of jeepney stops, additional bike parking facilities and construction of bikeways parallel to walkways are recommended in order to improve the accessibility of the study area.